2014
DOI: 10.1111/opo.12127
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical model of the contributions of corneal asphericity and anterior chamber depth to peripheral wavefront aberrations

Abstract: Both corneal asphericity and anterior chamber depth play important roles in determining peripheral wavefront aberrations. The two factors nonlinearly interact to affect peripheral aberrations. Higher corneal Q and/or shorter anterior chamber depth tend to produce relatively more myopic peripheral refraction. Increasing the Q value of the anterior surface of a contact lens might provide an interesting intervention to slow myopia progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…First, it includes few participants and a lack of anterior chamber depth measurement (ACD). He [ 32 ] reported that corneal asphericity and ACD play important roles in determining peripheral wavefront aberrations. However, Jo et al [ 33 ] suggested that the total HOAs change showed no correlation with ACD change before and after TLE using MMC.…”
Section: Discussionmentioning
confidence: 99%
“…First, it includes few participants and a lack of anterior chamber depth measurement (ACD). He [ 32 ] reported that corneal asphericity and ACD play important roles in determining peripheral wavefront aberrations. However, Jo et al [ 33 ] suggested that the total HOAs change showed no correlation with ACD change before and after TLE using MMC.…”
Section: Discussionmentioning
confidence: 99%
“…This is also in agreement with theoretical models, which assert that the more positive is Q, the more myopic is the peripheral refraction induced for M and J0. 22,23 Therefore, this fact should be considered by clinicians, because more prolate corneas might be expected to progress into more myopia. 24,25 For the naked eye, the sample showed a relative peripheral myopia lower than -0.50 D for M. We also found a trend for J0 to become more negative in both sides of the retina, whereas J45 becomes more negative with increasing eccentricity in the superior-nasal to inferior-temporal visual field.…”
Section: Discussionmentioning
confidence: 99%
“…It may help derive certain structural properties directly from optical features without going through blind optimization. Most of the previous studies in this field focus on the optical impacts of the optical components such as refracting surfaces [ 11 13 ], pupil size [ 14 ] and orientation of the ocular axes [ 15 ]. However, the optical contributions of those components are interdependent, which makes it hard to isolate the exact source of optical features.…”
Section: Introductionmentioning
confidence: 99%